2019
DOI: 10.1016/j.jfa.2019.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Fourier restriction implies maximal and variational Fourier restriction

Abstract: We give an abstract argument that an a priori Fourier restriction estimate for a certain choice of exponents automatically implies maximal and variational Fourier restriction estimates. These, in turn, provide pointwise and quantitative interpretations of restriction of the Fourier transform to the hypersurface in question.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…In [10], one of the present authors showed analogues of (1.3) and (1.6) when χ is replaced by a measure μ whose Fourier transform μ is C ∞ and satisfies the decay condition…”
mentioning
confidence: 76%
See 4 more Smart Citations
“…In [10], one of the present authors showed analogues of (1.3) and (1.6) when χ is replaced by a measure μ whose Fourier transform μ is C ∞ and satisfies the decay condition…”
mentioning
confidence: 76%
“…Subsequent papers [10] and [14], which appeared after the first version of the present paper, generalize the averaging procedure even further, by convolving f with certain averaging measures μ. In light of this more recent research, we now take the opportunity to both generalize (1.6) and complete our short survey of maximal and variational Fourier restriction theories with papers that appeared in the meantime.…”
mentioning
confidence: 99%
See 3 more Smart Citations